Global burden of hepatitis C: considerations for healthcare providers in the United States - Averhoff, Francisco M; Glass, Nancy; Holtzman, Deborah (Clinical infectious diseases, 2012)
An estimated 2%-3% of the world's population is living with hepatitis C virus (HCV) infection, and each year, >350 000 die of HCV-related conditions, including cirrhosis and liver cancer. The epidemiology and burden of HCV infection varies throughout the world, with country-specific prevalence ranging from <1% to >10%. In contrast to the United States and other developed countries, HCV transmission in developing countries frequently results from exposure to infected blood in healthcare and community settings. Hepatitis C prevention, care, and treatment programs must recognize country-specific epidemiology, which varies by setting and level of economic development. Awareness of the global epidemiology of HCV infection is important for US healthcare providers treating foreign-born patients from countries where HCV infection is endemic and for counseling patients who travel to these countries. Countries with a high burden of HCV infection also would benefit from establishing comprehensive prevention, care, and treatment programs.